2022
DOI: 10.1073/pnas.2200085119
|View full text |Cite
|
Sign up to set email alerts
|

The intracellular Ca 2+ channel TRPML3 is a PI3P effector that regulates autophagosome biogenesis

Abstract: Autophagy is a multiple fusion event, initiating with autophagosome formation and culminating with fusion with endo-lysosomes in a Ca 2+ -dependent manner. The source of Ca 2+ and the molecular mechanism by which Ca 2+ is provided for this process are not known. The intracellular Ca 2+ permeable channel transient receptor potential mucolipin 3 (TRPML3) localizes in the autophagosome and interacts with the mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 58 publications
(80 reference statements)
2
13
0
Order By: Relevance
“…Although our data clearly show that TRPML3/BK regulates autophagy, it remains unclear whether TRPML3/BK control autophagy induction, autophagy maturation, and/or autolysosomal degradation. To differentiate these possibilities, we adopted an autophagic flux assay by measuring LC3-II levels in the presence of bafilomycin A1 which inhibits autolysosomal degradation as well as the fusion of lysosomes with autophagosomes ( 2 , 42 ). We found that TRPML3 overexpression increased autophagic flux, and this was eliminated by Paxilline ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our data clearly show that TRPML3/BK regulates autophagy, it remains unclear whether TRPML3/BK control autophagy induction, autophagy maturation, and/or autolysosomal degradation. To differentiate these possibilities, we adopted an autophagic flux assay by measuring LC3-II levels in the presence of bafilomycin A1 which inhibits autolysosomal degradation as well as the fusion of lysosomes with autophagosomes ( 2 , 42 ). We found that TRPML3 overexpression increased autophagic flux, and this was eliminated by Paxilline ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TRPML3 is a Ca 2+ /Na + release channel, residing in both endosomal and lysosomal (endolysosomal) membranes. While TRPML1 is only activated by PI3,5P2, a PIP specifically localized in late endosomes and lysosomes ( 1 ), TRPML3 is activated by both PI3P, a PIP present in the phagophore and early endosomes, and PI3,5P2 ( 1 , 2 ). TRPML3 activity can also be enhanced by replacing luminal Na + with K + ( 3 6 ) and by increasing luminal pH ( 4 , 5 , 7 9 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PI(3)P binds to both cytosolic N-terminus and the large luminal loop. Interestingly, TRPML3 is activated by cytosolic but not luminal PI(3)P, but when combined, robust currents are observed (Kim et al, 2022) (Fig. 3).…”
Section: Coordinating Activation Of Other Tpc and Trpml Isoformsmentioning
confidence: 94%
“…TRPML1 and TRPML3 were not mechanosensitive. TRPML3 is a selective target of PI(3)P (Kim et al., 2022; Xu et al., 2023). PI(3)P binds to both cytosolic N‐terminus and the large luminal loop.…”
Section: Introductionmentioning
confidence: 99%